2023
DOI: 10.3866/pku.whxb202212020
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Heterogeneous Catalysis by Electronic Property Regulation of Single Atom Catalysts

Abstract: Past decades have witnessed the flourish of single atom catalysts (SACs) owing to their high atom-utilization efficiency and completely exposed active sites, which endows SACs with remarkably enhanced catalytic activities for various reactions. In the early development stage of SACs, researchers focus on the improvement of the catalytic performance of the catalysts, whereas the intrinsic catalytic reaction mechanism and the relationship between the electronic states of the metal sites and catalytic performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 134 publications
(191 reference statements)
0
6
0
Order By: Relevance
“…In the past decade, single atom catalysts (SACs) have received widespread attention in heterogeneous catalysis due to their 100% atom utilization, unique electronic structures, and tunable local coordination environment. , As novel cocatalysts in photocatalysis, SACs cooperatively work with semiconducting photocatalysts, achieving spatial charge separation and boosting photocatalytic performance. For HER, Pt is the most broadly studied cocatalyst due to its relatively large work function accepting photoexcited electrons and low overpotential for water reduction. Recent studies demonstrated that Pd SAs outperform Pt SAs in terms of HER. For instance, Schmuki and co-workers loaded different noble metal SAs (Pd, Pt, and Au) onto anatase titanium dioxide (TiO 2 ) nanosheets and compared their HER efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, single atom catalysts (SACs) have received widespread attention in heterogeneous catalysis due to their 100% atom utilization, unique electronic structures, and tunable local coordination environment. , As novel cocatalysts in photocatalysis, SACs cooperatively work with semiconducting photocatalysts, achieving spatial charge separation and boosting photocatalytic performance. For HER, Pt is the most broadly studied cocatalyst due to its relatively large work function accepting photoexcited electrons and low overpotential for water reduction. Recent studies demonstrated that Pd SAs outperform Pt SAs in terms of HER. For instance, Schmuki and co-workers loaded different noble metal SAs (Pd, Pt, and Au) onto anatase titanium dioxide (TiO 2 ) nanosheets and compared their HER efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…[13] The nature of the carrier, the unique active center's electronic symphony, and the coordination environment can greatly influence the chemical state and coordination structure of the metal single atoms, [14] and even regulate the adsorption and desorption behaviors of the reactants or products in the catalytic reaction to affect their enzyme-like activities. [15] Therefore, a more comprehensive understanding and regulation of the carrier types, local coordination microenvironment, and active centers of SACs can help to develop a new generation of nano-enzymatic materials for various biomedical applications (Figure 1). [16] First, Figure 1 illustrates that SAzyme can be rationally designed according to the structure of SAzyme by adjusting the carrier, the coordination environment of the first/second shell layer, and the metal active site to control the reactivity of SAzymes; in addition, Figure 1 illustrates the application of SAzyme in biosensing, tumor therapy, antibacterial, and anti-inflammatory therapies according to different development mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the interfacial sites between the metal nanoparticles and the support are highly support dependent and in many cases are the most catalytically active, e.g., the interfacial Pt–Nb alloy sites on Pt/Nb 2 CT x MXene have been reported to enhance the kinetics of the water–gas shift reaction . Deconvolution of the electronic effect on metal catalysis from the chemical effect specific to the support material is often a topic of discussion in the literature. ,, In this regard, non-Faradaic electrochemical modification of catalytic activity (NEMCA), initially proposed by Huggins, Mason, and co-workers and later developed by Vayenas and co-workers, , offers a conceptually straightforward method to isolate the effect of the Fermi level of metals on catalytic performance.…”
Section: Introductionmentioning
confidence: 99%